Seasonal herbage and animal production from three Cynodon species - Larbi, Asamoah; Mislevy, P.; Brown, W.F.; Adjei, M.B. (1990)
A study conducted to compare both seasonal forage production and animal performance on three Cynodon species; with particular reference on the nutritive value of these pasture grasses, mean seasonal herbage accumlation, carrying capacity, mean in vitro dry matter digestibility, and on the mean daily liveweight gain for steers.